Abrogation of Age‐Induced MicroRNA‐195 Rejuvenates the Senescent Mesenchymal Stem Cells by Reactivating Telomerase. (9th October 2015) - Okada, Motoi; Kim, Ha Won; Matsu‐ura, Kaoru; Wang, Yi‐Gang; Xu, Meifeng; Ashraf, Muhammad
Abstract : Previously, we reported that a novel subpopulation of young mesenchymal stem cells (YMSCs) existed in old bone marrow, which possessed high antiaging properties as well as excellent efficacy for cardiac repair. MicroRNAs (miRNAs) have emerged as key regulators in post‐transcriptional gene expression programs, and however, it is unknown whether miRNAs directly control stem cell senescence. Here we present the first evidence that miR‐195 overexpressed in old MSCs (OMSCs) induces stem cell senescence deteriorating their regenerative ability by directly deactivating telomerase reverse transcriptase ( Tert ), and abrogation of miR‐195 can reverse stem cell aging. MiRNAs profiling analysis in YMSCs and OMSCs by microarray showed that miR‐140, miR‐146a/b, and miR‐195 were significantly upregulated in OMSCs, which led us to hypothesize that these are age‐induced miRNAs involved in stem cell senescence. Of these miRNAs, we found miR‐195 directly targeted 3′‐untranslated region of Tert gene by computational target prediction analysis and luciferase assay, and knockdown of miR‐195 significantly increased Tert expression in OMSCs. Strikingly, miR‐195 inhibition significantly induced telomere relengthening in OMSCs along with reduced expression of senescence‐associated β‐galactosidase. Moreover, silencing miR‐195 in OMSCs by transfection of miR‐195 inhibitor significantly restored antiaging factors expression including Tert and Sirt1 as well as phosphorylation of Akt and FOXO1. Notably, abrogation of miR‐195 markedly restored proliferative abilities in OMSCs. Transplantation of OMSCs with knocked out miR‐195 reduced infarction size and improved LV function. In conclusion, rejuvenation of aged stem cells by miR‐195 inhibition would be a promising autologous therapeutic strategy for cardiac repair in the elderly patients. Stem Cells 2016;34:148–159